Turbidity and suspended solid reduction from palm oil mill effluent using coconut shell charcoal - Azmi, Nazatul Shima; Md. Yunos, Khairul Faezah (Faculty of Engineering, Universiti Putra Malaysia, 2012)
An attempt was made to the changes of turbidity and suspended solid of palm oil mill effluent (POME) using activated biocarbon (bio-char) made up from coconut shell. The complete study was done in batch mode to investigate the effect of various operating parameters. The effect of treatment time, adsorbent dosage, agitation speed and pH was significantly effect on the turbidity and suspended solid in POME. Using 0.5 g of coconut shell charcoal (CSC)/100 ml at pH 4.2 with 90 rpm agitation speed in 10 minute the turbidity and suspended solid was reduced up to 84.3 % and 86.7% respectively. As a huge reduction of turbidity and suspended solid in POME, it could be a lucrative technique for treatment of domestic wastewater generated in palm oil sectors.